If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 14 = 7x + -1 Reorder the terms: 14 + 4x = 7x + -1 Reorder the terms: 14 + 4x = -1 + 7x Solving 14 + 4x = -1 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 14 + 4x + -7x = -1 + 7x + -7x Combine like terms: 4x + -7x = -3x 14 + -3x = -1 + 7x + -7x Combine like terms: 7x + -7x = 0 14 + -3x = -1 + 0 14 + -3x = -1 Add '-14' to each side of the equation. 14 + -14 + -3x = -1 + -14 Combine like terms: 14 + -14 = 0 0 + -3x = -1 + -14 -3x = -1 + -14 Combine like terms: -1 + -14 = -15 -3x = -15 Divide each side by '-3'. x = 5 Simplifying x = 5
| -46-12x=-x+14 | | 5.5x+18=6.75+13 | | 8(-4x-2)+7x=-20x+11x-20 | | 150/100=x/17 | | x^2+10x-1232=0 | | 5(3n+10)+3(18-4n)=16 | | .85x=12 | | X-9.8=14.7 | | 14x^3-53x^2+41x-4=-4x^3+x^2+1x+4 | | X*y=33 | | 24+15w=249 | | 70/12= | | 6a-1a=9 | | 527/33.598= | | 527/33.589= | | (X-3)*(x-3)=-3 | | 2y-y-1=4 | | 8m+75=235 | | (7/10)/(3/4) | | 1.5(b+6)+9=4 | | (10x-7)+(5x-10)= | | 7z+11z=6 | | 16.95+8w=52.55 | | 33.598*33.598= | | y=-3x^2-2x+3 | | 10.7*3.14= | | 19408.4693=1/3*b*78.7 | | 8x-(10-3x)=6x-7 | | 9(54+6450)= | | f(x)=2x+39 | | -(2(3z-3)-(1+z))-(5(3-2z)-(1+2))=0 | | 3.14(14)(6)(2)= |